Intertextuality in Qurâ€™anic Studies: Ulum al-Qur'an Perspective on Utilization of the Bible in Qur'anic Interpretation - Saleh, Sujiat Zubaidi; Asnawi, Aqdi Rofiq; Hilda, Nurul Arifah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
In contemporary Qur'anic studies, a polemic has emerged regarding the use of the Bible as a reference to interpret the Qur'an, or what is categorized as intertextuality. This article aims to reveal the interpretive distortions that arise from the use of the Bible in interpreting the Qur'an by using the perspective of â€˜ulÅ«m al-Qurâ€™Än. The methodology of this research is qualitative by using the literature method and using the content analysis approach to analyze the data. Through this methodology, it is found that some orientalists such as Michel Cuypers and Edip Yuksel often use the Bible in interpreting the Qur'an (intertextuality). In the perspective of â€˜ulÅ«m al-Qurâ€™Än, this method of interpretation can be categorized as the use of isrÄ'Ä«liyyÄt in the interpretation of the Qur'an.Â  However, it turns out that what the orientalists did was not in line with the rules of using isrÄ'Ä«liyyÄt itself. Therefore, the intertextuality done by the orientalists can be classified as al-dakhÄ«l fÄ« al-tafsÄ«r (intrusion in interpretation). Ultimately, this method of interpretation is unacceptable, because it implies distortion of Qur'anic interpretation.